Genetic and Morphometric Variation of Marine Prawns, Penaeus Monodon Fabricius and Fenneropenaeus Merguiensis De Man in Malaysian Waters - Aziz, Dania (2011)
Marine prawns are divided into two common genera of Penaeus and Fenneropenaeus. Fenneropenaeus merguiensis is locally known as banana prawn while Penaeus monodon is tiger prawn. These prawns are widely distributed and are extensively cultured in the tropical and subtropical waters. Information on the genetic structure and diversity of natural populations for both the species is still limited eventhough it has long been exploited. Thus, the present study is to genetically characterize the wild and cultured populations by using morphological and microsatellite markers. A total of 16 populations were randomly selected representing 12 from Peninsular Malaysia and 4 from East Malaysia. Nineteen characters were measured using the conventional morphometric method and were analyzed according to the ratios of abdominal length and total length to reduce the allometric effects. The T-test analysis showed that the two species are statistically different from each other in the majority of the morphological traits. A total number of alleles per locus ranged from 3 to 9 with the allele size ranging from 100 to 300 base pairs. Overall FST value was high (73.4%), with great differentiation among the populations of both the species. FIT and FIS values were low but highly significant (P<0.05), suggesting a slight deficiency of heterozygosity. Chi-square (χ2) and likelihood ratio (G2) tests showed significant deviation (p<0.05) from Hardy-Weinberg equilibrium except for two loci. Considerable genetic distances were observed among all the populations with values ranging from 0.0103 to 0.6296. The genetic structure among the prawns within each region implies that mixing of individuals might have occurred, UPGMA dendrogram showed two major clusters, representing the two species. The wild and the cultured populations were also grouped separately. The genetic relationship between both the species was close, probably because the prawns are marine-estuarine species. There are no specific barrier to prevent migrations and genetic flow thus, there is still some form of interaction via migration and mating between the populations despite their geographical distance.